(untitled) (CIPEEX, 2025)
Although significant advances have been made in the discovery of plant-derived antimicrobials, research investigating the pharmacological properties of regional products remains scarce, particularly regarding the antibacterial potential of Psidium cattleyanum. Considering the ethnopharmacological use of this plant species for the treatment of respiratory tract diseases, and given that bacteria, along with viruses, constitute the etiological agents of many respiratory pathologies, this study aimed to investigate the antibacterial activity of the essential oil extracted from the aerial parts of this medicinal species. Microdilution broth tests were performed following Clinical and Laboratory Standards Institute (CLSI) recommendations, with modifications, against Gram-positive and Gram-negative microorganisms of four American Type Culture Collection (ATCC) standard strains. The results demonstrated that the essential oil from Psidium cattleyanum exhibits potential antibacterial activity. While one Escherichia coli strain showed resistance, the oil exhibited weak antibacterial activity against Pseudomonas aeruginosa and moderate activity against Staphylococcus aureus and S. epidermidis strains. Although preliminary, this research may open perspectives for the development of effective phytotherapeutics for infectious disease treatment.